Resource Management of Stakeholders in the Concept of Business Social Responsibility - Valentyna SHAPOVAL; Mariia BIELOBORODOVA; Tetyana HERASYMENKO; Natalia DUBROVA; Mykyta NECHEPURENKO (Communications of International Proceedings, 2021)
Business orientation on the strengthening of corporate social responsibility outlines for the organizations a new circle of actual problems connected with the organization.. To identify and assess the impact of stakeholders on activities organizations use models, matrices, and stakeholders maps. Building relationships with stakeholders is usually aimed at adapting a business to its environment. In turn, interaction with stakeholders presupposes active mutual influence through building various kinds of communications. The company must take into account the influence of stakeholders not only by the strategic plans but by project such decisions at a tactical level as well. In the course of interaction between enterprises and stakeholders, economic competitive relations and cooperation develop. In this research, we grouped the stakeholders of a socially responsible organization according to the resource approach and identified ways of interaction of stakeholders based on their satisfaction using the principle of Pareto-optimization.
Keywords: Stakeholder; CSR; quality; communication; cooperation.